UNDERSTANDING DISASTER PREVENTION LITERACY OF VILLAGERS IN MAGELANG REGENCY - Anisa Setya Arifina; Jaduk Gilang Pembayun; Mercedes Amanda (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
This research aims to measure the disaster literacy of residents in Disaster-prone Area (DPA) III and its support villages in Magelang Regency related to the Sister Village-based disaster mitigation. The four-level disaster literacy model (basic disaster literacy, functional disaster literacy, communicative/interactive literacy, and critical disaster literacy) is used to explain the manifestation of awareness, knowledge and understanding of DPA III villagers and their support villages regarding the Sister Village program. This qualitative research uses a constructivist approach. The data was collected through in depth-interview with research respondents, namely village officials and the Disaster Risk Mitigation Team in Ngargosoko, Nglumut, and Kapuhan villages (located in DPA III) as well as Sucen, Gulon and Mangunsari villages (support villages). The results showed that there are concrete manifestations of awareness, knowledge understanding and behavior of the villagers regarding the Sister Village program at these four levels. However, the context is preparedness or non-disaster and before disaster conditions. For example, the understanding of the table-top exercise and field exercise function held by BPBD Kabupaten Magelang. The function of the Sister Village program is to collect population and pre-existing facilities data on a regular basis, conduct awareness programs in accordance with respondents’ job description in the Sister Village program and map the aspects of disaster mitigation to minimize disaster risks. As for the condition during disaster and after disaster, it is still cannot be seen from the research results because at the time of the research, the respective community was not facing eruption disaster, given that the last Merapi eruption occurred in 2010 and the Sister Village program was only initiated a year later.